TEKNOLOGI PENDIDIKAN BERBASIS PELAJAR PANCASILA MENUJU INDONESIA EMAS - Hari Purwanto (JUPI (Jurnal Pendidikan Indonesia), 2023)
Technology in education has positive and negative impacts that cause various problems such as education that is too expensive, less relevant between education and needs and lack of educational equity. World progress is motivated by advanced education, therefore changes in the national education system must continue to be carried out so that education in Indonesia has better quality. The purpose of this study is to find out how to develop education towards a golden Indonesia, this study uses a qualitative approach with interview data collection techniques and literature study. Data collection techniques are focused on three aspects of sources, namely based on the findings of problems that occur in the field and the results of interviews from the subjects studied. The conclusion of the results of this study is the need for comprehensive social change including improving the quality of teachers, education systems and students.